Persepsi Mahasiswa Perempuan Terhadap Keberadaan Akun Instagram @umcantik_id - Nailah Zulfa Khairunnisa; Naila Naswa Salsabila; Nahlatus Salsabilah (Jurnal Wanita dan Keluarga, 2026)
Social media has become a public space that highlights the importance of physical appearance and influences how individuals judge their appearance. One phenomenon that has emerged in Indonesia is the existence of beautiful campus accounts, such as @unpad.geulis, @ugmcantik, @ubcantikid, and @unejcantik. Women are often objectified on social media, so we wanted to study the Instagram account @umcantik_id to explore female students' perceptions of the existence of the “umcantik_id” account at Malang State University. The method used is qualitative research with an exploratory approach design that aims to find out “what happened,” “seek new insights,” and "assess phenomena from a new/different perspective (Saunders et al., 2009). The results obtained reveal four stages. The input stage includes sources of information exposure and motivation to follow the @umcantik_id account, the processing stage includes cognitive beauty schemas, the evaluation stage includes subjective interpretation of the @umcantik_id account, and the output stage includes the impact and expectations of the @umcantik_id account. Suggestions for further research include using documentary studies of post comments, exploring male informants, conducting follow-up studies on informants whose photos were posted on the @umcantik_id account, and involving the account administrator as one of the informants to obtain more perspectives. Keywords: Beauty Account, female student, perception.